Italian-Canadian Artists Luigi Nasato and Giovanni Gerometta and the Indigenous Images in Their Mosaic Murals - Pugliese, Olga Zorzi (Italian Canadiana)

(untitled) (Iter Press, 2022)
In addition to presenting a general appreciation of the lives and artistic contributions of Luigi Nasato and Giovanni Gerometta, this article, which is based on live interviews, photographic and written documents, and the artists’ sketches and maquettes, discusses four original mosaic murals designed and executed by the two Italian Canadians in the 1960s, 1980s, and 1990s for public buildings in Edmonton, Toronto, Montreal, and Quebec City. The works treat themes of Indigenous life, multiculturalism, communication, and marine transportation. All depict Indigenous figures and demonstrate how the traditional art form of mosaic became a vehicle for Canadian content, even if no profound knowledge of Native Canadians or their culture is demonstrated or could have been, given the political and social landscape of Canada then and even now.